2009
DOI: 10.3171/2008.12.jns08441
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in brain arteriovenous malformations after embolization using Onyx or N-butyl cyanoacrylate

Abstract: Onyx penetrates much smaller vessels than NBCA. Inflammation occurs with both embolic agents at equal frequency. Evidence of chronic foreign-body giant cells and recanalization after Onyx embolization shows a long-standing reaction to Onyx and raises questions about the permanence of occlusion after Onyx embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 31 publications
2
67
2
1
Order By: Relevance
“…In a case of Onyx embolization with same-day surgical resection, no evidence of associated inflammatory infiltrate was noted. In four brain AVMs surgically resected one day after embolization, mild acute inflammatory reaction was seen in two cases (14,15). We observed moderate amount of vascular inflammation in cases 2 and 3, who were embolized with PHIL only.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In a case of Onyx embolization with same-day surgical resection, no evidence of associated inflammatory infiltrate was noted. In four brain AVMs surgically resected one day after embolization, mild acute inflammatory reaction was seen in two cases (14,15). We observed moderate amount of vascular inflammation in cases 2 and 3, who were embolized with PHIL only.…”
Section: Discussionmentioning
confidence: 81%
“…6). Natarjan et al (15) reported the smallest vessel occluded by Onyx to be 5 μm with an average diameter of 81.4±103.8 µm. Jahan et al (14) reported blood vessels ranging from 80 µm to 1 mm in diameter filled with the embolic material.…”
Section: Discussionmentioning
confidence: 99%
“…Organ ischemia or patient-specific factors might be responsible for the pain experienced in some cases. Since the polymerization of NBCA involves an exothermic reaction, it can result in the destruction of the vessel wall and the perivascular tissue [39,64,126]. It also causes pain; however, the mechanism responsible for this is unknown.…”
Section: International Situationmentioning
confidence: 99%
“…In addition, adhesive liquid embolic materials (15)(16)(17)(18), including cyano acid isobutyl fatty acid and its derivatives, are most commonly used in clinical practice. However, their limitations include adhering easily to the high-molecular microcatheter, which subsequently blocks the catheter.…”
Section: Discussionmentioning
confidence: 99%